STRENGTHENING AI-BASED CRITICAL LITERACY IN LITERATURE LEARNING UNDER THE MERDEKA CURRICULUM - Ni Komang Sabina Sanji Putri; Ida Ayu Agung Ekasriadi (Universitas Muhammadiyah Makassar, 2026)
Literature learning in the era of digital transformation requires the strengthening of students’ critical literacy so they can interpret, evaluate, and construct meaning reflectively, not merely understand texts literally. The emergence of artificial intelligence (AI) offers opportunities to enrich literature learning, yet creates risks of dependence on instant answers when not pedagogically guided. This study examined the effectiveness of an AI-based literature learning model in improving students’ critical literacy and described their responses to AI integration under the Merdeka Curriculum. The study employed a quantitative approach with a nonequivalent control group quasi-experimental design. The population consisted of 360 eleventh-grade students at public senior high school in Kediri City, Indonesia. A total of 120 students were selected through purposive sampling and divided into an experimental group and a control group, each consisting of 60 students. The instruments included a critical literacy test consisting of 20 essay questions, a student response questionnaire, and an observation sheet. The treatment was implemented over six weeks through 12 learning sessions. Data were analyzed using descriptive statistics, paired sample t-test, independent sample t-test, gain score, and Cohen’s d. The results showed that the experimental group increased from 56.4 to 84.7, while the control group increased from 55.9 to 67.2. The independent sample t-test on gain scores indicated a significant difference, with t=12.47, p=0.000, and Cohen’s d=1.82. Student responses were positive, with 86.7% stating that AI supported critical thinking. These findings indicate that AI-based literature learning is effective and relevant for strengthening critical literacy in Merdeka Curriculum.